Entrepreneurship-Based Leadership Model in Strengthening Institutional Quality and Reputation - Muhammad Alfi Alfaridli; Abdullah (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This research focuses on the development of an entrepreneurial leadership model to strengthen the quality and reputation of educational institutions, using a case study of Ulil Albab Islamic Senior High School (SMA IT Ulil Albab). The research objective is to analyze the characteristics of the principal's entrepreneurial leadership, the mechanisms of its influence on quality management, and its contribution to the institution's reputation. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using the Miles and Huberman model through data condensation, data presentation, and conclusion drawing and verification. The results show that the principal's entrepreneurial leadership is characterized by innovative, visionary, collaborative characteristics, and the courage to take calculated risks. These characteristics directly influence the transformation of the organizational culture to become more adaptive, creative, collaborative, and spiritually valuable. This cultural change strengthens the implementation of quality educational services through innovative programs, increased teacher participation, and active student involvement. In addition, entrepreneurial leadership contributes significantly to improving the institution's reputation, as demonstrated by increased public trust, expanded partnership networks, and the school's visibility in the public sphere. The implications of this research confirm that entrepreneurial leadership is a key strategy for integrated Islamic educational institutions to increase competitiveness in the era of disruption. This leadership model can be adopted by other school principals to encourage innovation, strengthen quality, and build a sustainable institutional image. This research also provides a theoretical contribution by mapping the integrative relationship between entrepreneurial leadership, organizational culture, educational quality, and institutional reputation in the context of Islamic education.